Emulsão à base de carvacrol em modelo de envelhecimento animal induzido por d-galactose - Dantas, Sabine Helena (2021)
Introduction: Aging is a process characterized by a gradual decline in cellular, molecular and tissue functions. Evidence suggests that the accumulation of senescent cells associated with oxidative stress has been implicated in the promotion of various diseases in the elderly, including cardiovascular diseases, which are considered the greatest cause of morbidity and mortality in the world. In this sense, in order to delay or mitigate the effects of aging, the search for new natural sources with antioxidant activity has aroused a lot of interest. Objectives: To identify scientific evidence on the effect of plants and their metabolites on cardiovascular aging in an animal model induced by D-galactose; evaluate the cardioprotective effect of carvacrol in an aging model induced by D-galactose, and propose the deposition of a patent, being an emulsion based on carvacrol, which has cardioprotective properties in an animal aging model induced by D-galactose. Method: This is a pre-clinical experimental study, structured in three stages: in the first, an attempt was made to identify scientific evidence from an integrative review with search for scientific articles in the Web of Science, Scopus and Medical Literature databases Analysis and Retrievel System On-line (MEDLINE / PubMed), using the indexed descriptors aging, D-galactose cardiovascular diseases, Boolean operator and strategy Population, Interest and Context (PICo), from February to July 2020, with period of publication from 2012 to 2019. The second stage was a pre-clinical experimental study in which the cardioprotective effect of carvacrol was evaluated in an animal D-galactose-induced aging model. For this, 8-9 week old rats were divided into four experimental groups: vehicle-treated control group (CTL), 250mg / kg D-galactose group (Dgal) and 50mg / kg D-galactose + carvacrol groups. and 100mg / kg (Dgal + C50 and Dgal + C100), respectively, being submitted to daily administrations, intraperitoneal (D-galactose) and oral (carvacrol), during eight weeks of treatment. The third stage involved filing a patent, characterized as an emulsion based on carvacrol. Results and Discussion: the data obtained in the first stage included the analysis of 8 articles that demonstrated beneficial effects of plants and their metabolites on cardiovascular aging in a D-galactose-induced aging model. In step two, the data obtained in the research demonstrated that carvacrol was able to promote a cardioprotective effect on oxidative stress and arterial hypertension in rats aged by D-galactose.The results obtained in the first two stages of the study supported the patent filing proposal, presented as a carvacrol-based emulsion, with the following composition: carvacrol oil, solubilized in cremofor® and diluted in physiological saline, in order to be the desired doses were obtained for each experimental protocol. Final considerations: After demonstrating the cardioprotective effects in a preclinical study against D-galactose-induced aging model, it was proposed to construct a patent, characterized as an emulsion based on carvacrol, to be deposited, and which presents a strong potential for therapeutic use to be tested including in clinical studies.